Ahmad Aiman As-Syukree, diploma graduate from France, chooses UMPSA - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 8 March 2025 – Ahmad Aiman As-Syukree, a diploma graduate from the Institut Universitaire Technologie de Tours (IUT de Tours), France, officially registered today as a new student at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) to further his studies in the Bachelor of Electrical Engineering with Honours.